Bahasa Inggris - Angga Nofrendiko; Khairuddin Khairuddin; Yendrizal Yendrizal; Padli Padli; Fiky Zarya (Jurnal Penelitian Pendidikan IPA, 2024)
This study investigates the problem of low dribbling ability in soccer players at the Special Sports School (SKO) SMA 4 West Sumatra. The main objective of this study was to determine the influence of speed, agility and concentration on dribbling performance. A quantitative approach with descriptive methods was used, involving 34 student-athletes from SKO SMA 4 West Sumatra. Data was collected using a 30-meter dash test for speed, Illinois Agility Test for agility, Grid Concentration Exercise for concentration, and Dribbling Test for dribbling ability. Path analysis was used to evaluate the relationship between variables. The results showed that speed (β = 0.435, p < 0.01) has a significant direct effect on dribbling ability, indicating that higher speed improves dribbling ability. Agility (β = 0.403, p < 0.01) also significantly improved dribbling performance, as more agile players showed better dribbling ability. Concentration (β = 0.435, p < 0.01) directly affected dribbling, with focused players maintaining better control and stability while dribbling. These findings suggest that a training program targeted at improving these attributes is essential for improving dribbling ability in soccer players